New Partnership for Africa's Development : Macroeconomics, Institutions, and Poverty - Nsouli, Saleh (International Monetary Fund, 2004)
Adopted in 2001, the New Partnership for Africa's Development (NEPAD) represents a new vision to place African countries on a path toward poverty reduction, sustainable growth, and full integration in the world economy. This conference volume includes papers selected from a high-level seminar in December 2002 held in Dakar, Senegal, organized by the IMF Institute in the context of the program of the Joint Africa Institute (JAI). The papers focus on the challenges confronting NEPAD in reducing poverty, promoting trade, attracting capital flows, and effecting institutional reforms.